2007
DOI: 10.1634/stemcells.2006-0561
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow-Derived Mesenchymal Stem Cells Promote Neuronal Networks with Functional Synaptic Transmission After Transplantation into Mice with Neurodegeneration

Abstract: Recent studies have shown that bone marrow-derived MSCs (BM-MSCs) improve neurological deficits when transplanted into animal models of neurological disorders. However, the precise mechanism by which this occurs remains unknown. Herein we demonstrate that BM-MSCs are able to promote neuronal networks with functional synaptic transmission after transplantation into Niemann-Pick disease type C (NP-C) mouse cerebellum. To address the mechanism by which this occurs, we used gene microarray, whole-cell patch-clamp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
129
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(133 citation statements)
references
References 43 publications
2
129
0
2
Order By: Relevance
“…Pathological characteristics are progressive Purkinje neuron loss, intracellular accumulation of sphingomyelin, cholesterol and neuroglial cell (astrocyte, microglial cell) infiltration in the cerebellum [6,11]. Our studies have shown that transplantation of bone marrowderived mesenchymal stem cells (BM-MSC) results in alleviation of pathology associated with murine NP-C cerebellum through fusion of BM-MSC and Purkinje neuron and promotion of neuronal networks with functional synaptic transmission [1][2][3]. Herein, we assessed the therapeutic effects of conditionally immortalized multipotential neural stem cells (NSCs), Maudsley hippocampal clone 36 (MHP36), in a NP-C model mice.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…Pathological characteristics are progressive Purkinje neuron loss, intracellular accumulation of sphingomyelin, cholesterol and neuroglial cell (astrocyte, microglial cell) infiltration in the cerebellum [6,11]. Our studies have shown that transplantation of bone marrowderived mesenchymal stem cells (BM-MSC) results in alleviation of pathology associated with murine NP-C cerebellum through fusion of BM-MSC and Purkinje neuron and promotion of neuronal networks with functional synaptic transmission [1][2][3]. Herein, we assessed the therapeutic effects of conditionally immortalized multipotential neural stem cells (NSCs), Maudsley hippocampal clone 36 (MHP36), in a NP-C model mice.…”
mentioning
confidence: 87%
“…The NP-C Gsbs GFP+ mice were created by crossing NP-C mice with Gsbs GFP+ mice, which carry a null allele of Gsbs (GeneBank accession No. 1333876) on BALB/c back ground and concomitantly have the green fluorescent protein (GFP) reporter gene inserted into the Gsbs locus [2,6]. Animals were housed on a 12 hr light/dark cycle and given water and food ad libitum.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Mesenchymal stem cells can also be differentiated into neurons, astrocytes, tenocytes, skeletal myocytes and cells of visceral mesoderm (endothelial cells). [10][11][12][13][14] Bone targeting of culture-expanded murine MSC by ectopic expression of murine a4 integrin Despite the potential of MSC in tissue regeneration, a major limitation remains in the delivery of ex vivo modified MSC to target tissues upon autologous transfer. In our recent study, we have shown that ectopic expression of a4 integrin on mouse MSC resulted in significant increase in bone specific retention of transplanted mouse MSC.…”
Section: Isolation Expansion and Phenotyping Of Mscmentioning
confidence: 99%
“…A number of investigations have demonstrated that cell-based transplantation therapies have been proven to be promising strategies for relieving symptoms of various neuronal diseases and improving function of damaged neuronal tissues in experimental models (Bae et al 2007;Dezawa et al 2005;Lu et al 2001). As reported by Hu et al, glial restricted precursor cells (GRPs) and Schwann cells (SCs) were co-grafted into normal or injured spinal cord.…”
Section: Introductionmentioning
confidence: 99%